A new approach for the computation of design shear force in reinforced concrete walls subjected to seismic loads - Seckin, Aytug; Doran, Bilge (WILEY, 2023)
This paper investigates the dynamic shear amplification in reinforced concrete shear walls designed according to the seismic provisions of the current Turkish Building Earthquake Code (TBEC-2018). Shear walls with a high ductility level and different aspect ratios are examined to evaluate the design shear force calculated by using the dynamic amplification factor (beta(v)) and overstrength factor (D) defined in TBEC-2018. For this purpose, response spectrum analyses (RSAs) are first carried out on two-dimensional cantilever shear walls with heights of 30, 45, and 60 m and with lengths of 1.5, 3, and 4.5 m in the plan. Then, a total of 198 nonlinear time history analyses (NLTHAs) are performed with real and simulated ground motions matched to the elastic design spectrum defined in TBEC-2018. The comparison of the design shear forces obtained from RSA and the shear demands obtained from NLTHA along the heights of the walls reveals that the design shear forces calculated according to TBEC-2018 may underestimate the actual shear demands from studied ground motions. Moreover, the applicability of the updates proposed to TBEC-2018 for the design shear force and shear force diagram along the wall height in reinforced concrete shear wall-frame systems to cantilever shear walls is also examined.
Keywords: dynamic shear amplification; nonlinear time history analysis; reinforced concrete shear wall; seismic shear demand; TBEC-2018; DEMAND; PERFORMANCE; BUILDINGS; EARTHQUAKE; Construction & Building Technology; Engineering